FPGA Based V/f Control of Three Phase Induction Motor Drives Integrating Super-Lift Luo Converter - Elangovan P; Nalin Kant Mohanty (Institute of Advanced Engineering and Science, 2015)
The significance of Elementary Positive Output Super-Lift Luo Converter (EPOSLLC) in constant Voltage/Hertz (V/f) controlled Induction Motor (IM) drive is presented. The traditional IM drive which integrates phase controlled rectifier or boost converter in the facade end upshot tribulations like DC link fluctuations and deprived DC link voltage level. To overcome the problem, the conventional DC-DC converter is replaced with Proportional plus Integral (PI) controlled EPOSLLC in the front end of IM drive that produce the DC link voltage in geometric progression. The Voltage Source Inverter (VSI) of the suggested system renders both open loop and closed loop V/f control scheme for IM by feedback regulated Sinusoidal Pulse Width Modulation (SPWM) technique. Simulation and experimental works are conceded and results presented to demonstrate the viability of the proposed approach. Simulation is carried out using MATLAB /SIMULINK software and the experimental setup is built with Field Programmable Gate Array (FPGA) Spartan-6 processor. The anticipated EPOSLLC is found fit for V/f controlled IM drives considering the DC link Voltage, Speed response of IM and Total Harmonic Distorion (THD) in IM current.